ARTICULATE: A European glossary of terms used in oral health professional education. (8th March 2022) - Davies, Julia R.; Field, James; Dixon, Jonathan; Manzanares‐Cespedes, Maria‐Cristina; Vital, Sibylle; Paganelli, Corrado; Akota, Ilze; Quinn, Barry; Roger‐Leroi, Valerie; Murphy, Denis; Gerber, Gabor; Tubert‐Jeannin, Stephanie
Abstract: Introduction: The Erasmus+O‐Health‐EDU project aims to gain a comprehensive view of oral health professional (OHP) education in Europe, through the development of web‐based surveys and online toolkits. A glossary to facilitate a common language through which academic teams could cooperate and communicate more accurately was identified as a key need within the project. The aim of ARTICULATE was thus to create a shared language, with a European focus, for terms and concepts used in the field of OHP education. Methods: The methodology was developed from those published for construction of other glossaries with a circular and iterative process: the creation of content and definitions by a group of experts in OHP education, the testing of "fitness for purpose" of the content, and stakeholder consultation. All creation steps were followed by refinements based on testing results and stakeholder comments. The final glossary was then launched as an online resource including a built‐in mechanism for user feedback. Results: The scope and structure of the glossary were mapped out at a workshop with 12 dental education experts from 7 European countries. A total of 328 terms were identified, of which 171 were finally included in ARTICULATE. After piloting with a close group of other colleagues, the glossary was opened for external input. Thirty European Deans or Heads of Education assessed the definition of each term as "clear" or "not clear." A total of 86 definitions were described as "clear" by all individuals. Terms deemed unclear by at least one individual were revisited and changes made to 37 of the definitions. In conjunction with the launch of the glossary, a range of stakeholder organisations were informed and asked to participate in an open global consultation by providing feedback online. Since its launch in June 2021, the ARTICULATE website (https://o‐health‐edu.org/articulate ) has had an average of 500 visits/month. To promote community ownership, forms embedded on the ARTICULATE webpage allow users to give feedback and suggest new terms. A standing taskforce will meet regularly to consider amendments and make changes to ensure that the glossary remains a relevant and up‐to‐date resource over time. Conclusion: ARTICULATE is a unique, evolving, online glossary of terms relating to OHP education, created as a resource for all interested OHP educators. The glossary is a key output of the O‐Health‐Edu project, which relies on a comprehensive vision of OHP education to address the future oral health needs of the European population.